Accidental ingestion of a cocktail stick - Kaoutzanis, Christodoulos (BMJ Publishing Group, 2010)
Cocktail stick (CS) ingestion injury has rarely been reported in the literature. It is a serious clinical problem with considerable morbidity and mortality, largely due to the fact that the event is unnoticed by the patient. We report a case of CS ingestion that went unrecognised by the patient and caused a perforation in the mid-small bowel. We discuss how injuries from such events can become a diagnostic challenge. The history should be re-evaluated in any undiagnosed abdominal pain which has an unclear aetiology and negative radiology.